Terapi Herbal Sari Mentimun untuk Menurunkan Tekanan Darah pada Penderita Hipertensi - Hermawan, Nur Sefa Arief; Novariana, Nana (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2018)
The focus of this study was the decrease in blood pressure of systole and diastole in hypertension patients after administration of cucumber extract. The purpose of this study to determine the effect of herbal therapy (extract cucumber) against the decrease in blood pressure in patients with hypertension. Subjects in this study were all hypertensive patients at Puskesmas (Public Health Centre) Kedaton, Bandar Lampung, Indonesia with a total sample of 30 respondents. This research was conducted by giving cucumber extract for three days during morning, noon and night. The results showed that herbal therapy (cucumber extract) gives the effect of decreased blood pressure on hypertensive patients. The result of t test showed the decrease score of systole blood pressure with p value 0,001 (p less than 0,05) and at the decrease of diastole blood pressure obtained p value 0,001 (p less than 0,05). Based on the results of cucumber research can be used as an alternative trita in hypertensive patients using herbal medicine. It is expected that researchers next do research on herbal therapy with other types of plants.